Development and validation of a new reverse-phase high-performance liquid chromatography (RP-HPLC) method for the quantifications of tolperisone loaded in liposomes - Rawan N. AlKaraki; Rula R. Haddadin; Shahed K. Tarawneh; Marwa A.M. Alimari; Rehan M. Alkasasbeh; Tebat Al-ferdous E. Shamaileh; Mustafa S. Almohtaseb; Malek G. Hajaya (Results in Chemistry)
Tolperisone (TOL) is a muscle relaxant that tends to undergo uncontrollable degradation in the intestinal medium, leading to low oral bioavailability and the generation of genotoxic degradants. This study aimed to assess the possibility of using liposomes as an alternative carrier system that can alleviate the uncontrolled degradation of TOL, and to develop a reverse-phase, high performance liquid chromatography (RP-HPLC) method for the detection and quantification of TOL in liposomes. Effective isocratic chromatographic separation of TOL was accomplished using Sunniest C-18 column, acetonitrile: methanol: water (60:20:20) mixed with 5.5 v/v% triethylamine as a mobile phase. The flow rate of the mobile phase was 0.6 mL/min, column temperature was 35 ± 0.2 °C, and the injection volume was 10 μL. TOL retention time was 6.93 min, at a wavelength of 251 nm. The developed method was found to be specific, accurate (>98 %), precise (%RSD < 2 %), and reliable for TOL detection and quantification in the presence of liposomes matrix. The method's applicability was demonstrated by accurately quantifying TOL content in a commercial pharmaceutical formulation. The validated RP-HPLC method was used to demonstrate the suitability of liposomes as a carrier for TOL by evaluating its entrapment efficiency (14.76 %), along with achieving a slower drug in-vitro cumulative percentage release in the targeted media (compared to free TOL solution) from the liposomes.